The Expression of Epistemicity in British Internet Discussion Forums in Contrast with Newspaper Opinion Articles and Political Speeches - Marta Carretero (Anglica. An International Journal of English Studies)
This paper sets forth a quantitative analysis of expressions of epistemicity, a category covering the expression of commitment to the information transmitted, in a corpus of 25 threads extracted from British discussion forums. Epistemicity is divided into three categories: epistemic modality, evidentiality and factivity, each divided into subcategories. The results are analysed in contrast to comparable corpora of newspaper opinion articles and political speeches. The analysis uncovers significant differences in the expression of epistemicity in the three genres, in terms of both frequency and distribution across categories, the subcategory ‘cognitive attitude’ being a case in point. Epistemicity in the discussion forums is also proved to display features of orality and routinisation.